Effect of species and particle size on essential oil yield of citrus peel (Citrus spp) - JALGAONKAR, KIRTI R; JHA, S K; PAL, R K; JHA, G K; SAMUEL, D V K (The Indian Journal of Agricultural Sciences, 2026)
Essential oil was extracted from the peel of four citrus species namely, Jatti Khatti, Soh Sarkar, grapefruit and pummelo using Clevenger apparatus. All the four species yielded significantly different essential oil. The mean essential oil yield of 8.08, 4.64, 4.77 and 3.79% (db) was obtained from Jatti Khatti, Soh Sarkar, grapefruit and pummelo, respectively. Particle size of peel was found to have significant influence on oil yield. Oil yield of 0.68% was obtained from whole peel, whereas peel of 0.5 mm size exhibited maximum yield, increasing it by about 13%. Analysis of oil indicated that number of volatile compounds in grapefruit was 16, whereas in Jatti Khatti, Soh Sarkar and pummelo, these compounds were 14, 11 and 6, respectively. Limonene, the major compound was found to vary from 93.57-96.41% in the essential oil. Physical and chemical properties of essential oil revealed better quality of essential oil from grapefruit..